ENHANCING DUAL EDUCATION THROUGH VIDEO-BASED LEARNING: PEDAGOGICAL AND TECHNOLOGICAL PERSPECTIVES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The dual education system integrates theoretical instruction with practical workplace training, requiring flexible and effective learning resources. Videobased learning has emerged as a powerful tool to support this model by bridging the gap between educational institutions and industry environments. This study explores the role of video lessons in dual education, focusing on their pedagogical value, technological requirements, and impact on students’ professional competencies. The research employs qualitative analysis of existing educational practices and examines the effectiveness of instructional videos in improving learning outcomes, motivation, and accessibility. The findings indicate that well-designed video lessons significantly enhance students’ understanding of professional concepts and support continuous learning in dual education systems.